2020
DOI: 10.1111/1750-3841.15377
|View full text |Cite
|
Sign up to set email alerts
|

Effect of isochoric freezing on quality aspects of minimally processed potatoes

Abstract: The enhanced interest in greater convenience foods has recently led to the expansion of minimally processed potato products. This study investigated the effects of isochoric freezing on pre‐peeled potato cubes, including quality attributes (microstructure, texture, and color), nutritional value (ascorbic acid (AA) content, total phenolic content, and antioxidant capacity), and polyphenol oxidase activity. Isochoric freezing (−3 °C/30 MPa) was compared with isobaric freezing (−3 °C/0.1 MPa) and individual quick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 39 publications
1
21
0
4
Order By: Relevance
“…However, the increase in mass was significantly lower for these samples (2.3%) than for water-immersed potatoes (13.6%), since potato samples were in osmotic equilibrium with the AA solution. A previous study found no changes in the cellular tissue of potatoes frozen at −3 °C under isochoric conditions, suggesting that the slight increase in mass was probably due to the pressure-induced impregnation of the intercellular spaces in the potato tissue with the external solution [ 15 ]. This effect highlights isochoric freezing as an interesting tool for nutrient diffusion into the intercellular spaces and pores of solid foods.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the increase in mass was significantly lower for these samples (2.3%) than for water-immersed potatoes (13.6%), since potato samples were in osmotic equilibrium with the AA solution. A previous study found no changes in the cellular tissue of potatoes frozen at −3 °C under isochoric conditions, suggesting that the slight increase in mass was probably due to the pressure-induced impregnation of the intercellular spaces in the potato tissue with the external solution [ 15 ]. This effect highlights isochoric freezing as an interesting tool for nutrient diffusion into the intercellular spaces and pores of solid foods.…”
Section: Resultsmentioning
confidence: 99%
“…For vacuum-packed samples and those immersed in water, BI values increased with a decrease in temperature. Previous authors have also found that isochoric freezing substantially reduced browning in potatoes but does not prevent it [ 15 , 16 ]. This might be due to the destruction of potato tissues and loss of cell compartmentalization at higher pressures and the subsequent increased interactions between polyphenolic substrates and PPO.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations